2014
DOI: 10.4103/0976-0105.134983
|View full text |Cite
|
Sign up to set email alerts
|

A study of potential adverse drug-drug interactions among prescribed drugs in medicine outpatient department of a tertiary care teaching hospital

Abstract: Objective:To evaluate prevalence, types, and severity of potential adverse drug-drug interaction in medicine out-patient department.Materials and Methods:A single-point, prospective, and observational study was carried out in medicine OPD. Study began after obtaining approval Institutional Ethics Committee. Data were collected and potential drug-drug interactions (pDDIs) were identified using medscape drug interaction checker and were analyzed.Result:A total of 350 prescriptions with mean age 52.45 ± 14.49 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 8 publications
3
33
4
Order By: Relevance
“…It was similar to the study conducted by Patel et al, 2011, Riechelmann et al, 2007, Riechelmann et al, 2008, Dinesh et al, 2007 Of the pDDIs (n=390) observed, majority were of pharmacodynamic (n=202, 51.80%) in nature followed by pharmacokinetic (n=188, 48.20%). These findings were contrast to the study reported by Vonbach et al, 2008 andAparasu et al, 2007. Most frequent DDI was seen between Metformin + Ranitidine (moderate interaction) in 70 prescriptions (50%) and between Ranitidine + Acetaminophen (minor interaction) in 48 prescriptions (34.29%). The common major interactions were seen between Rabeprazole + Clopidogrel in 4 prescriptions (2.86%), Enalapril + Spironolactone and Ciprofloxacin + Tramadol in 3 prescriptions (2.14%).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was similar to the study conducted by Patel et al, 2011, Riechelmann et al, 2007, Riechelmann et al, 2008, Dinesh et al, 2007 Of the pDDIs (n=390) observed, majority were of pharmacodynamic (n=202, 51.80%) in nature followed by pharmacokinetic (n=188, 48.20%). These findings were contrast to the study reported by Vonbach et al, 2008 andAparasu et al, 2007. Most frequent DDI was seen between Metformin + Ranitidine (moderate interaction) in 70 prescriptions (50%) and between Ranitidine + Acetaminophen (minor interaction) in 48 prescriptions (34.29%). The common major interactions were seen between Rabeprazole + Clopidogrel in 4 prescriptions (2.86%), Enalapril + Spironolactone and Ciprofloxacin + Tramadol in 3 prescriptions (2.14%).…”
Section: Discussionsupporting
confidence: 84%
“…Adding each drug combination increases chances of further DDI. Special attention and thorough monitoring is definitely required for the patients who are at the most risk of developing pDDIs (Rana et al, 2014). Now-a-days, many patients are on polypharmacy for treating their disease conditions and there are many interactions between the drugs prescribed in each prescription.…”
Section: Introductionmentioning
confidence: 99%
“…and Sepehri et al . [2223] Surprisingly, nine serious reactions were observed with ondansetron. However, their potential to cause serious DDI has been neglected by prescribers.…”
Section: Discussionmentioning
confidence: 99%
“…Up to our knowledge, studies concerning the nature and prevalence of pDDIs in the outpatient department (OPD) of Pakistani hospitals remains unaddressed. Some studies from the developed countries have reported a prevalence rate of 28–83% for pDDIs in OPD [ 4 , 14 , 16 19 ]. These studies are limited by the nature of study settings, design, DDIs screening tool, and drug prescribing pattern.…”
Section: Introductionmentioning
confidence: 99%